Academ's fury - Butcher, Jim (New York Ace Books, 2005)
The precarious alliance between the people of Alera and the furies is thrown into disarray by the death of the First Lord of Alera, and the fate of the Alerians lies in the hands of Tavi, an untried young man who must draw on his courage to save his world.
113882
Keywords: Fantasy fiction; Alera (Imaginary kingdom) -- Fiction; Teenage boys -- Fiction; Warriors -- Fiction; War stories; Good and evil -- Fiction; Fantasy fiction; Science fiction